USING PICTURE MEDIA TO ENHANCE WRITING ABILITY IN PROCEDURE TEXT - Mewa Ameliah; Ummi Khaerati Syam; Nunung Anugerawati; Ismail Sangkala; Nurdevi Bte Abduh (Universitas Muhammadiyah Makassar, 2019)
The use of procedure text is described how something is accomplished through a sequence of actions or steps. Students can find procedure texts in game rules, cooking recipes, and using ATM machines. It is helpful for the students in learning procedure in writing. This research aimed at finding out the improvement of students’ writing ability in procedure text by using picture media at the Eleventh Grade of SMA Negeri 2 Takalar. It employed Classroom Action research. This research consisted of two cycles. One cycle had been conducted, wherein cycle consisted of four meetings. It employed the writing test as an instrument. A number of subjects of the research were 33 students in class eleventh conducted with 24 women and 9 men. The results of the student's writing test in the cycle I had good scores. In the cycle I, the students’ achievement of content was 7.77. In the other hand the students’ achievement of organization in cycle I was 7.5. From the findings indicated that the students’ achievement in writing ability in cycle 1 reached the standard target achievement KKM 7.5. From these findings, the researcher concluded that by using Picture Media could improve the students’ writing ability in procedure text at the eleventh grade of SMA Negeri 2 Takalar.